Islamic Republic of Afghanistan : Staff Report for the 2005 Article IV Consultation and Sixth Review Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation highlights that over the last 12 months, the Afghan authorities have made further progress in rebuilding institutions and stabilizing the economy. In a challenging environment, dominated by the difficult security situation and parliamentary elections, the authorities have continued to pursue prudent fiscal and monetary policies and have implemented a number of important institutional and structural reforms that have contributed to strong growth, moderate inflation, a stable exchange rate, and fiscal consolidation. The authorities have also modernized central bank operations and reinforced its supervision capacity.